Manado’s Consumptive Lifestyle: A Lived Religion Perspective to Construct Contextual Pastoral Theology - Leonardo Caesar Dendeng; Agnes B.J. Raintung; Novita P. Sianturi; Melkisedek Teleng (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article develops a pastoral theology that is suitable for the lifestyle and context of individuals in Manado, serving as contextual pastoral counselling. Similar to how theology is influenced by its context, pastoral theology is similarly shaped by its specific context. Despite its inclusion within Indonesia, the background of Manado diverges from that of other locations in the country. Consequently, the pastoral theology perspective that is formulated will also vary. By employing the techniques of observation and literary analysis from a lived religion perspective, it was determined that the pastoral approach developed in Manado originates from the setting of a prominent consumerist lifestyle, which is characteristic of the people in Manado within the larger Indonesian society. The commonly repeated statement that is said to support this lifestyle is "biar kalah nasi mar jang kalah aksi" (even if you don't eat, you have to be stylish). This extravagant lifestyle has the potential to create issues within the family and give rise to numerous other familial problems, as it is associated with excessive spending or squandering of significant amounts of money.